Optimization of Extraction and HPLC-MS/MS Profiling of Phenolic Compounds from Red Grape Seed Extracts Using Conventional and Deep Eutectic Solvents - Nevena Dabetic; Vanja Todorovic; Andjelija Malenovic; Sladjana Sobajic; Bojan Markovic (MDPI AG, 2022)
Winemaking generates large quantities of grape waste consisting of seeds, skin and stalks. Given that grape seeds are a rich source of different bioactive compounds, the main goal of this research was to optimize grape seed phenol extraction using a Box-Behnken design. The following conditions were derived from the optimization process: sample:solvent ratio of 1:10 w/v, extraction time of 30 min and extraction temperature of 50 °C. In addition, a sustainable (green) approach for obtaining extracts was developed by comparing choline chloride:citric acid-ChCit (natural deep eutectic solvent (NADES)) and ethanol extraction methods with respect to phenol profiles and antioxidant activity. This study was conducted on seeds from eight different red grape varieties. Phenolic acids, flavan-3-ols and procyanidins were characterized using HPLC-MS/MS, and the concentration of procyanidin B1 was above 1 mg/g of dry weight in all analyzed samples. The contents of all phenol classes and antioxidant activities were found to not differ significantly between the solvents, but NADES was found to offer valuable advantages. Importantly, ChCit showed a strong affinity toward procyanidins and a strong correlation between antioxidant activity and quantified phenolic compounds.